2013
DOI: 10.1007/s00401-013-1129-2
|View full text |Cite
|
Sign up to set email alerts
|

N-truncated amyloid β (Aβ) 4-42 forms stable aggregates and induces acute and long-lasting behavioral deficits

Abstract: N-truncated Aβ4-42 is highly abundant in Alzheimer disease (AD) brain and was the first Aβ peptide discovered in AD plaques. However, a possible role in AD aetiology has largely been neglected. In the present report, we demonstrate that Aβ4-42 rapidly forms aggregates possessing a high aggregation propensity in terms of monomer consumption and oligomer formation. Short-term treatment of primary cortical neurons indicated that Aβ4-42 is as toxic as pyroglutamate Aβ3-42 and Aβ1-42. In line with these findings, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
351
2
32

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 155 publications
(429 citation statements)
references
References 71 publications
(97 reference statements)
37
351
2
32
Order By: Relevance
“…Next, we investigated how brain endothelial LRP1 deficiency affects AD-related behavior by examining spatial learning and memory (40,41). We used three different tests to examine motor deficits, string suspension, inverted grip, and balance beam, and found that no mice in any tested group showed abnormalities (Supplemental Figure 6).…”
Section: Deletion Of Lrp1 In Brain Endothelium Results In Reduced [mentioning
confidence: 99%
“…Next, we investigated how brain endothelial LRP1 deficiency affects AD-related behavior by examining spatial learning and memory (40,41). We used three different tests to examine motor deficits, string suspension, inverted grip, and balance beam, and found that no mice in any tested group showed abnormalities (Supplemental Figure 6).…”
Section: Deletion Of Lrp1 In Brain Endothelium Results In Reduced [mentioning
confidence: 99%
“…The N-terminal region of A␤ is host for a wide range of events such as phosphorylation (23), metal binding (28,42), tyrosine nitration (43), and truncation (19,20). These events may modulate the role of A␤ in oxidative damage (44) and induction of inflammation (45) and alter the efficiency of prionlike self-propagation (24) and their interaction with biological targets such as cellular lipid membranes (46).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that the N-terminal region of A␤ is mainly unstructured in these fibrillar models, several lines of evidence point to an important role of this region in pathogenic aggregation. In particular, it has been shown that toxic A␤ assembly is enhanced by mutations in this region (A2V, H6R, or D7N) (17,18) as well as N-terminal truncation with or without pyroglutamate formation (19,20). Furthermore, antibodies against the N-terminal region inhibit A␤ amyloid formation (21), and the conformational propensity of the N-terminal region controls the partitioning between A␤ oligomers and protofibrils (22).…”
mentioning
confidence: 99%
“…Surprisingly, no beneficial effects on working memory, extracellular Ab plaque load, neuron loss, as well as hippocampal neurogenesis could be detected. 25 A direct link between intraneuronal Ab accumulation and subsequent neuron loss in distinct brain regions has been also established in mouse models like TBA2.1 34 or Tg4-42, 35 engineered to directly overexpress mutant Ab peptides in the absence of mutant APP overexpression. These models use the neuronspecific Thy1-promotor to overexpress the N-terminal truncated Ab species Ab3-42 or Ab4-42 and are characterized by extensive CA1 neuron loss and associated behavioral deficits.…”
Section: Neuron Loss In Transgenic Ad Mouse Modelsmentioning
confidence: 99%
“…These models use the neuronspecific Thy1-promotor to overexpress the N-terminal truncated Ab species Ab3-42 or Ab4-42 and are characterized by extensive CA1 neuron loss and associated behavioral deficits. [34][35][36] In the Tg4-42 model, enhanced physical activity using enriched housing in cages equipped with running wheels resulted in an amelioration of CA1 neuron loss, accompanied by a significantly increased overall dentate gyrus granule cell number and a concomitant increase in the number of DCX-positive cells in the DG. 26 So far, no accumulation of Ab peptides within dentate gyrus neurons has been reported in any of the mouse models that have been studied.…”
Section: Neuron Loss In Transgenic Ad Mouse Modelsmentioning
confidence: 99%